Status of and Future Research on Thermosensory Processing - Mizunami, Makoto; Nishino, Hiroshi; Yokohari, Fumio (Frontiers in Physiology, 2016)
Thermosensation is critically important for survival of all animals. In the cockroach Periplaneta americana, thermoreceptor neurons on antennae and thermosensory interneurons in the antennal lobe have been characterized electrophysiologically, and recent studies using advanced transgenic technologies in the fruit fly Drosophila melanogaster have added much to the knowledge of these neurons, enabling us to discuss common principles of thermosensory processing systems in insects. Cockroaches and many other insects possess only one type of thermoreceptor neurons on antennae that are excited by cooling and inhibited by warming. In contrast, the antennae of fruit flies and other dipterans possess oppositely responding warm and cold receptor neurons. Despite differences in their thermoreceptive equipment, central processing of temperature information is much the same in flies and cockroaches. Axons of thermoreceptor neurons project to the margin of the antennal lobe and form glomeruli, from which cold, warm and cold-warm projection neurons originate, the last neurons being excited by both cooling and warming. Axons of antennal lobe thermosensory projection neurons of the antennal lobe terminate in three distinct areas of the protocerebrum, the mushroom body, lateral horn and posterior lateral protocerebrum, the last area also receiving termination of hygrosensory projection neurons. Such multiple thermosensory pathways may serve to control multiple forms of thermosensory behavior. Electrophysiological studies on cockroaches and transgenic approaches in flies are encouraged to complement each other for further elucidating general principles of thermosensory processing in the insect brain.